2018
DOI: 10.3168/jds.2018-14992
|View full text |Cite
|
Sign up to set email alerts
|

Carcass characteristics of cattle differing in Jersey proportion

Abstract: Comparison of alternative dairy (cross-)breeding programs requires full appraisals of all revenues and costs, including beef merit. Few studies exist on carcass characteristics of crossbred dairy progeny originating from dairy herds as well as their dams. The objective of the present study was to quantify, using a national database, the carcass characteristics of young animals and cows differing in their fraction of Jersey. The data set consisted of 117,593 young animals and 42,799 cows. The associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 24 publications
6
40
1
Order By: Relevance
“…The tenderness of the meat leads to better results than that of several young animal breeds specialized in meat production (Costa et al, 2002;Waritthitham et al, 2010;Bureš and Barton, 2012) and could be used as a marketing factor for the sale of a differentiated product with added value. The good meat quality is in agreement with a previous study by Berry et al (2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The tenderness of the meat leads to better results than that of several young animal breeds specialized in meat production (Costa et al, 2002;Waritthitham et al, 2010;Bureš and Barton, 2012) and could be used as a marketing factor for the sale of a differentiated product with added value. The good meat quality is in agreement with a previous study by Berry et al (2018).…”
Section: Discussionsupporting
confidence: 92%
“…In countries with developed dairy farming, dairy male calves are used for meat production and represent a significant portion of the meat consumed by the population. According to Berry et al (2018), the contribution of beef output to the revenue of dairy enterprises is well recognized. Van der Werf et al (1998) suggested that surplus calves and culled cow sales constituted 10 to 20% of the gross income from a dairy herd.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once sufficient replacement females are deemed to have been generated, most dairy producers will tend to use beef bulls to maximize the subsequent calf value; in their analysis of calves from dairy herds sold at less than 42 d of age, McHugh et al (2010) clearly demonstrated a superior value of beef × dairy cross male calves relative to dairy × dairy male calves. In their analysis of a national database of slaughtered cattle, Berry et al (2018) also demonstrated a greater carcass value of beef (in this case, Angus) × dairy animals relative to dairy × dairy animals.…”
Section: Resultsmentioning
confidence: 98%
“…The weighted mean carcass weight PTA of the beef AI bulls used was 15 kg heavier than the dairy AI bulls, and the conformation score, which is measured on a scale of 1 to 15 (Englishby et al, 2016), was 1.71 units superior in the beef bulls. The superior conformation score of progeny from dairy herds sired by beef sires relative to those sired by dairy sires has already been established (Campion et al, 2009;Berry et al, 2018). The raw mean reliability of the beef bulls used was higher than that of the dairy bulls used for all traits, although it was more variable in the former.…”
Section: Raw Meansmentioning
confidence: 98%